Position Validation of the Dwarfing Gene Dw6 in Oat (Avena sativa L.) and Its Correlated Effects on Agronomic Traits - Yan, Honghai; Yu, Kaiquan; Xu, Yinghong; Zhou, Pingping; Zhao, Jun; Li, Ying; Liu, Xiaomeng; Ren, Changzhong; Peng, Yuanying (Frontiers in Plant Science, 2021)
An F6:8 recombinant inbred line (RIL) population derived from the cross between WAOAT2132 (Dw6) and Caracas along with the two parents were used to evaluate the genetic effects of Dw6 dwarfing gene on plant height and other agronomic traits in oat (Avena sativa L.) across three environments, and develop closely linked markers for marker-assisted selection (MAS) for Dw6. The two parents differed in all investigated agronomic traits except for the number of whorls. The RIL lines showed a bimodal distribution for plant height in all three tested environments, supporting the height of this population was controlled by a single gene. Dw6 significantly reduced plant height (37.66%~44.29%) and panicle length (13.99%~22.10%) but without compromising the coleoptile length which was often positively associated with the reduced stature caused by dwarfing genes. Dw6 has also strong negative effects on hundred kernel weight (14.00%~29.55%), and kernel length (4.21%~9.47%), whereas the effects of Dw6 on the kernel width were not uniform across three environments. By contrast, lines with Dw6 produced more productive tillers (10.11%~10.53%) than lines without Dw6. All these together suggested the potential yield penalty associated with Dw6 might be partially due to the decrease of kernel weight which is attributed largely to the reduction of kernel length. Eighty-one simple sequence repeat (SSR) primer pairs from chromosome 6D were tested, five of them were polymorphic in two parents and in two contrasting bulks, confirming the 6D location of Dw6. By using the five polymorphic markers, Dw6 was mapped to an interval of 1.0 cM flanked by markers SSR83 and SSR120. Caution should be applied in using this information since maker order conflicts were observed. The close linkages of these two markers to Dw6 were further validated in a range of oat lines. The newly developed markers will provide a solid basis for future efforts both in the identification of Dw6 in oat germplasm and in the determination of the nature of the gene through positional cloning.